Examining the chronic disease health literacy of First Nations Australians: A mixed methods study - Rheault, Haunnah (Queensland University of Technology, 2022)
Chronic disease is the most significant contributor to the mortality gap between Australia’s First Nations people and the overall Australian population. This study explored chronic disease self-management and health literacy in First Nations adults living in remote Queensland. Key findings were poor communication by healthcare providers coupled with limited health literacy abilities of individuals were the major barriers to active engagement with managing chronic disease. Providing a supportive health literacy environment and the provision of appropriate health information delivered in a cultural safe way using clinical yarning, may assist with closing the gap in First Nations people.